Optimalisasi Pemilihan Laptop Kerja Terbaik dengan Pendekatan Metode AHP dan TOPSIS - Sya’Roni; Entin Sutinah; Nani Agustina (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2025)
The components found in laptops are generally the same as those in personal computers (PCs), but they are designed to be smaller, lighter, and more energy-efficient. As technology has advanced, laptops have also undergone many improvements, including in design, processor speed, memory capacity, feature additions, and efficiency in terms of time and space. Additionally, the prices of laptops today are relatively affordable. PT. Varsindo Kimia Abadi is a company engaged in the chemical industry. Currently, the company is facing a challenge in selecting the right laptop for new employees, considering the many brands and specifications available. Therefore, the author aims to provide the best recommendations for laptop selection. In the data analysis process of this research, two methods are adopted: AHP (Analytic Hierarchy Process) and TOPSIS (Technique for Order Preference by Similarity to Ideal Solution). The research results indicate that the best choice for a work laptop is the Asus X441MA with a score of 0.6717, followed by the Lenovo Ideapad IP V130 with a score of 0.5913, and the Asus X407MA as the third alternative with a score of 0.5458.